2010
DOI: 10.1007/s00330-010-1975-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relevant hepatic steatosis in obese adolescents by rapid fat-selective GRE imaging with spatial-spectral excitation: a quantitative comparison with spectroscopic findings

Abstract: Fat-selective MR imaging provides both a reliable and a convenient method of rapidly quantifying IHL content in obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Springer and colleagues studied 29 obese adolescents in Tubingen, Germany. [21] All exams were performed at 1.5 Tesla. Spectroscopy was performed using the stimulated echo acquisition mode (STEAM) technique without T2 correction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Springer and colleagues studied 29 obese adolescents in Tubingen, Germany. [21] All exams were performed at 1.5 Tesla. Spectroscopy was performed using the stimulated echo acquisition mode (STEAM) technique without T2 correction.…”
Section: Resultsmentioning
confidence: 99%
“…Both clinicians and radiologists need to be aware that – due to the presence of confounding factors such as T1 relaxation, T2(*) decay, multi-frequency interference effects of protons in fat [6, 7, 18, 20, 21], noise bias[22], and eddy currents[23] – conventional MRS and MRI methods may be inaccurate, non-robust, and non-reproducible. Advanced MRS and MRI methods address these confounders to estimate the proton density fat fraction, a standardized biomarker of liver fat content that is accurate[5, 7, 36] reproducible across different scanners[37, 38] and field strengths[37, 38], and robust to routine acquisition parameter changes that are common in clinical practice and may occur in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Data from adolescents and adults, who participated in two studies in Tübingen, Germany, were included in this analysis. The adolescents participated in the Tübingen DISKUS study in which subjects were enrolled when having either a body mass index (BMI) > 99.5th percentile or > 90th percentile and at least one of the following metabolically relevant conditions: family history of type 2 diabetes, impaired glucose tolerance, or acanthosis nigricans . Adults participated in the Tübingen Lifestyle Intervention Program (TULIP), which was designed as a longitudinal intervention study for adult subjects at risk of developing insulin resistance and type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Various imaging modalities, including magnetic resonance imaging, computed tomography, and US, have been used to assess patients with hepatic steatosis in a noninvasive fashion, with magnetic resonance imaging validated as the most accurate and effective method and US as the most cost‐effective . Although studies in children have shown that magnetic resonance imaging measurements were strongly correlated with the histologic grades of fat in liver with high sensitivity and specificity, its applicability in the pediatric population is limited because of the high cost and the requirement for sedation . Computed tomography, on the other hand, is not widely accepted as a method of choice because of the ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%